2019
DOI: 10.1186/s13049-019-0624-4
|View full text |Cite
|
Sign up to set email alerts
|

Repeated ambulance use is associated with chronic diseases - a population-based historic cohort study of patients’ symptoms and diagnoses

Abstract: Background There is a growing demand for emergency medical services (EMS) and patients are repeatedly transported by ambulance services. For many patients, especially those with chronic disease, there may be better ways of delivering care. We examined the symptom at time of emergency call and the hospital diagnosis for those ambulance users who repeatedly received an ambulance. Methods Population-based historic cohort study of patients receiving an ambulance after an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…The rate of chest pain patients transported by ambulance was comparable to the chest pain rate found in recent Swedish and Danish studies, but substantially higher than earlier reported in studies from Norway and the UK [2, 2023]. The most likely reason for this higher rate is a temporal increase in chest pain cases also reported in other studies [23, 24].…”
Section: Discussionsupporting
confidence: 78%
“…The rate of chest pain patients transported by ambulance was comparable to the chest pain rate found in recent Swedish and Danish studies, but substantially higher than earlier reported in studies from Norway and the UK [2, 2023]. The most likely reason for this higher rate is a temporal increase in chest pain cases also reported in other studies [23, 24].…”
Section: Discussionsupporting
confidence: 78%
“…Despite having completed a specialist degree in ambulance care, the respondents felt that they lacked in‐depth knowledge about various mental disorders and comorbidities, particularly when patients had been exposed to different traumas. Several studies have shown that people with mental disorders, besides having more health problems and less adherence to medications, also tend to be at higher risk of complications after severe trauma, such as self‐inflicted injury, attempted suicide or penetrating trauma, where one‐third of major trauma patients had used alcohol, drugs or a medication overdose at the time of admission (Byles et al., 2014; Clous et al., 2017; Dekker et al., 2020; Holden et al., 2010; Lundin et al., 2016; Søvsø et al., 2019; Wang et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] So far, studies on patient characteristics associated with contacting an acute health care setting have either included patients contacting EMS or OOH-PC and mostly focus has been on inappropriate or recurrent use. [4][5][6][7][8] However, possible overlaps in the EMS and OOH-PC patient populations have been observed; some patients in need of acute care contact OOH-PC and some patients with non-specific complaints perhaps more suitable for OOH-PC contact EMS. [9][10][11][12] Besides the patient's self-perceived urgency and severity of the acute health problem, other factors play a role in the choice of entrance to out-of-hours (OOH) care.…”
Section: Introductionmentioning
confidence: 99%